Guided neural regeneration with autologous fat grafting and oxygen hyperbaric therapy - Gustavo Lopes TOLEDO; Beatriz Sobrinho SANGALETTE; Larissa Camargo PASSEROTTI; Juliana de Almeida NASCIMENTO; André Luis SHINOHARA; Alexandre Leite Rodrigues de OLIVEIRA; Marília Afonso Rabelo BUZALAF; Antônio de Castro RODRIGUES (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The loss of continuity of the nerve structure interrupts the transmission of nerve impulses and leads to the disorganization of functional activities. Many methods, as the use of neurogenic factors, aid in the process of neural regeneration by accelerating or improving peripheral nerves neoformation. The adipose tissue is abundant in the human body, and it has presented promising results in the regeneration of peripheral nerves. We carried out a randomized controlled study in 9 months, using 45 male Wistar rats, 80 days old, and the sciatic nerve was chosen for analysis. The control animals were divided into three groups - Initial group (IG), Final group (FG), and denervated group (DG) - with seven animals each. The experimental groups, with twelve animals each, were polyethylene tube filled with fat (EGF) and polyethylene tube without filling (EGwf). All groups, except IG, were submitted to 10 sessions of hyperbaric oxygen treatment of 1h 45 min in alternating days. Functional evaluation by walking-track was assessed using the Catwalk XT® software and tissues were harvested and stained with 1% toluidine blue for histological analysis. Quantitative data were first analyzed with the Kolmogorov Smirnov normality test. Comparison between the four groups was analyzed by ANOVA followed by Tukey Test. We concluded that hyperbaric oxygen therapy had positive results on morphometric and functional parameters. However, no significant differences were found regarding the use of autologous fat graft.